PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN - NI LUH CANDRA EKA PUTRI; I Putu Julianto; Gusti ayu ketut rencana sari dewi (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2026)
This study aims to analyze the effect of capital structure, profitability, and firm size on firm value in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange during the period 2020–2024. Firm value is measured using Price to Book Value (PBV), capital structure is measured by Debt to Equity Ratio (DER), profitability is measured by Return on Assets (ROA), and firm size is measured by the natural logarithm of total assets. This study uses a quantitative approach with a causal research design. The data used are secondary data obtained from the companies’ financial statements. The data analysis method employed is panel data regression with model selection using the Chow test and Hausman test. The results show that capital structure has a positive and significant effect on firm value, profitability has no significant effect on firm value, and firm size has a negative and significant effect on firm value. These findings indicate that financing decisions and firm scale play an important role in determining firm value, while profitability does not necessarily influence investor perceptions.